The

reversal and negation

of the constituents of the conditional

\[\begin{equation*} P \implies Q \end{equation*} \]

in the form

\[\begin{equation*} \lnot Q \implies \lnot P, \end{equation*} \]

which, unlike the converse and inverse, is

equivalent to the original statement,

that is

\[\begin{equation*} (P \implies Q) \equiv (\lnot Q \implies \lnot P) \end{equation*} \]

For example, the molecular statement, “if you dance, you sweat” is equivalent to “if you do not sweat, you do not dance”.

For example, the statement

“if you are dancing, you are sweating”

is equivalent to

“if you not sweating, you are not dancing”.

© 2024 Rudolf Adamkovič under GNU General Public License version 3.

Made with Emacs and secret alien technologies of yesteryear.